2020
DOI: 10.3390/en13051224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reducing Pollutant Emissions in Selected Heating and Ventilation Systems in Single-Family Houses

Abstract: The article presents the results of a study aiming to select the optimal source of heat for a newly designed single-family home. Commercial software was used to compare heating and ventilation systems involving a bituminous coal boiler, a condensing gas boiler, a biomass boiler, a heat pump with water and glycol as heat transfer media. The effectiveness of natural ventilation, mechanical ventilation with a ground-coupled heat exchanger, and solar heater panels for water heating were evaluated. The analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…The structure of the Polish energy balance, which produces 5% of electricity produced throughout the European Union, is significantly different from the structures from the European Union countries due to the highest coal consumption in the energy sector. The Polish energy industry restructuring in Poland has been carried out for many years in order to achieve the assumed ecological goals in the European Union [38][39][40][41][42][43][44]. The transformation of the energy market depends on the financial conditions of companies from energy sectors which are currently exposed to high financial risk in Poland [45][46][47][48][49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The structure of the Polish energy balance, which produces 5% of electricity produced throughout the European Union, is significantly different from the structures from the European Union countries due to the highest coal consumption in the energy sector. The Polish energy industry restructuring in Poland has been carried out for many years in order to achieve the assumed ecological goals in the European Union [38][39][40][41][42][43][44]. The transformation of the energy market depends on the financial conditions of companies from energy sectors which are currently exposed to high financial risk in Poland [45][46][47][48][49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…When a condensing gas boiler is used as a reference heat source, according to Gajewski et al, the air-to-water heat pump is neither an economically viable nor environmentally beneficial solution [19]. Another more comprehensive (considering more heat sources) study by Hałacz et al revealed that a condensing boiler with natural ventilation in case of single-family houses is, pollutant emission-wise, the most favorable solution [20]. The above-mentioned studies support the argument that the country-specific energy mix has a significant impact on the "greenness" In the months of 2018 In recent years, multiple studies have been dedicated to the analysis of heat pumps' role in shrinking the heating sector's carbon footprint.…”
Section: Introductionmentioning
confidence: 99%
“…The Regulation of the Minister of Infrastructure and Development on the methodology to determine the energy performance of a building and energy performance certificates [6] presents in detail the calculation procedure to obtain energy performance indicators: EP (nonrenewable primary energy), EK (final energy), and EU (usable energy). This procedure has been presented by several authors recently [7][8][9][10][11][12][13][14][15]. The base to obtain EP, EK, and EU is calculated annual energy use for space heating; cooling; ventilation; domestic hot water (DHW); and, in nonresidential buildings, lighting.…”
Section: Introductionmentioning
confidence: 99%